An expert system based on Discrete Wavelet Transform - ANFIS for acquisition and recognition of invariant features from texture images - Avci, Derya; Poyraz, Mustafa; Leblebicio?lu, Mehmet Kemal (Institute of Electrical and Electronics Engineers Inc., 2015)
Texture is low-level image features. Today, texture analysis is applied to different fields such as ultrasound images recognition, document classification, classification of radar imagery, texture-based image retrieval. Texture analysis and classification is an important issue. Comparison of texture analysis and classification was characterized by the lack of adequate methods. Wavelet decomposition method is superior to other conventional methods. In this study, Discrete Wavelet Transform (DWT) - Adaptive Network Based Fuzzy Inference System (ANFIS) were used for acquisition and recognition invariant properties of tissue-type image. 22 texture images were taken from Brodatz database for the analysis of tissue-type image. 50 randomly 64 × 64 regions are selected from each of 22 images. Testing Success with the average rate of 91.27% was obtained by using DWT-ANFIS method. © 2015 IEEE.
Doku Tipi Imgelerden De?işmez Özelliklerin Elde Edilmesi ve Tanlnmasi Için Ayrik Dalgacik Dönüşümü-UATBÇS Tabanli Bir Uzman Sistem
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: adaptive network-based fuzzy inference system; discrete wavelet transform; entropy; Expert systems; texture images